Age-Related Progression of Microvascular Dysfunction in Cystic Fibrosis: New Detection Ways and Clinical Outcomes - Kreslová, M; Sýkorová, A; Bittenglová, R; Schwarz, J; Pomahačová, R; Jehlička, P; Kobr, J; Trefil, L; Sýkora, J (Physiological research, 2021)
There are concerns about altered vascular functions that could play an important role in the pathogenesis and influence the severity of chronic disease, however, increased cardiovascular risk in paediatric cystic fibrosis (CF) has not been yet fully understood. Aim was to analyse vascular disease risk and investigate changes over times in CF and controls. We prospectively enrolled 22 CF subjects (a median age of 16.07 years), and 22 healthy demographically matched controls (a median age of 17.28 years) and determined endothelial function. We utilised a combined diagnostic approach by measuring the plethysmographic Reactive Hyperemia Index (RHI) as the post-to preocclusive endothelium-dependent changes of vascular tone, and biomarkers that are known to be related to endothelial dysfunction (ED): asymmetric dimethyl arginine (ADMA), high-sensitive CRP (hsCRP), VCAM-1 and E-selectin. RHI values were significantly lower in CF young adults (p<0.005). HsCRP (p<0.005), E-selectin (p<0.001) and VCAM-1 (p<0.001) were significantly increased in CF patients since childhood. The findings have provided a detailed account of the ongoing process of microvascular dysfunction with gradual progression with the age of CF patients, making them further at risk of advanced vascular disease. Elevations of biomarkers in CF children with not yet demonstrated RHI changes but with significantly reduced RHI in adulthood and lipid profile changes indicate the possible occurrence of ED with CF-related specific risk factors over time and will enable us to provide the best possible support.
Keywords: Disease Progression; Male; Endothelium, Vascular; progrese nemoci; mladiství; mužské pohlaví; studie případů a kontrol; Prospective Studies; Adult; mladý dospělý; Hyperemia; dítě; Cystic Fibrosis; Child; věkové faktory; hyperemie; Young Adult; ženské pohlaví; Humans; prospektivní studie; biologické markery; cévní endotel; Age Factors; Case-Control Studies; dospělí; Biomarkers; Female; Adolescent; lidé; cystická fibróza